Accumulation and translocation of heavy metals in water hyacinth: Maximising the use of green resources to remediate sites impacted by e-waste recycling activities. (August 2020) - Du, Yongming; Wu, Qihang; Kong, Deguan; Shi, Yongfeng; Huang, Xuexia; Luo, Dinggui; Chen, Zhenxin; Xiao, Tangfu; Leung, Jonathan Y.S.
Graphical abstract: Highlights: The capacity of water hyacinth for remediating contaminated sites was evaluated. Water hyacinth could increase heavy metal uptake in the more contaminated sites. Translocation of heavy metals from the roots to the leaves was low (TF < 1). The leaves can be safely used as animal feed (c.f. guideline levels), except sheep. Water hyacinth is a good candidate to remediate sites contaminated with heavy metals. Abstract: Abandoned e-waste recycling sites can still cause heavy metal pollution in the nearby aquatic environment, where the heavy metals in sediment can be remobilized and dispersed by water current. Water plants may be used to prevent the dispersal of heavy metals and remediate contaminated sites without substantially disturbing the environment. Here, we examined the degree of heavy metal contamination in sediment along a river (Lian River, South China) previously influenced by e-waste recycling activities, and evaluated the capacity of water hyacinth for remediating contaminated sites by measuring the accumulation and translocation of heavy metals. We found that the sediment adjacent to the abandoned e-waste recycling site was still heavily contaminated ( Igeo  > 3) with various heavy metals (Ag, Cd, Cu, Pb, Sb, Sn and Zn), which can disperse to the nearby region via water current. Water hyacinth not only accumulated a variety of heavy metals (i.e. non-selective uptake), but also increased their uptake and translocation in the more contaminated sites, indicating its good capacity to remove heavy metals from water. Nevertheless, the concentrations of heavy metals in the edible part of water hyacinth (i.e. leaves) were still far below the maximum tolerable levels as animal feed (except Cu for sheep) due to the limited translocation. This study provides important insights into the possibility of using water hyacinth as the natural resource for multiple purposes (e.g. animal feed and biofuel) in addition to remediation of contaminated sites.